Using focus groups to inform a brief video intervention to reduce public stigma toward Black youth living with psychosis - Jankowski, Samantha E.; Pope, Leah G.; Smith, Stephen; Pagdon, Shannon; Dixon, Lisa B.; Amsalem, Doron (Frontiers in Psychiatry, 2023)
Objective: Black individuals living with psychosis are at risk for stigma and marginalization due to systematic discrimination and barriers to receiving treatment. Social contact-based interventions have the potential to reduce stigma; however, interventions with elements specific to the experiences of Black youth are limited. Therefore, we aimed to gather input from Black youth living with psychosis to develop a social contact-based, brief video intervention to reduce public stigma toward Black youth with psychosis.Methods: Two 90-minute focus groups were conducted with seven young Black individuals ages 18-30 with First Episode Psychosis from OnTrackNY. Participants were asked about their experiences of stigma and racial discrimination, and their perspectives on a video intervention. Focus group transcripts were analyzed using thematic content analysis.Results: Themes that emerged included: the salience of stigma and racial experiences for some participants and not others; the linking of religiosity and symptoms in Black communities; the importance of taking responsibility for recovery as a coping strategy to counteract stigma; and mixed views on creating a video intervention specific to Black youth.Conclusions: Meaningful and empowering involvement of individuals with lived experience of psychosis is essential to create stigma reducing interventions. Input from Black youth living with psychosis assisted in developing a culturally tailored brief video-based intervention to reduce public stigma toward Black youth with psychosis that included information about the protagonist's experience of race and mental illness, specifically family, religious, and community-based experiences.